The landscapists redefining landscape relations - Wall, Ed (Oxford John Wiley & Sons, 2020)
Who defines the landscapes around us? What practices are employed as contemporary landscapes are produced? This issue argues that landscapes are made and remade through interrelations between people and the world around them, from geographers investigating the lives of urban wastelands to landscape architects projecting future cities, and from migrants navigating border systems to artists working with local residents. In contrast to tendencies to emphasise the physical forms of landscapes, with their potential to be redesigned and represented in
drawings, this issue brings to the forefront the social constructedness of landscapes by focusing on a range of critical practices and daily actions. As conventional frames of landscape are challenged, other ways of measuring, mapping, imagining, designing, building and occupying them are revealed. For centuries, artists and designers have represented landscapes of power in paintings and have transformed them through their design proposals. But in recent years a number of researchers, designers, artists and activists have explored an expanded
field of landscape, investigating populations fleeing conflict zones, reimagining cities facing ecological challenges, questioning territorial claims, and critiquing processes of urbanisation. This issue focuses on some of these individuals whose work and livews encompass a
diverse range of practices, brought together through their critical redefinition of landscape relations.
tAbout the guest editor, Ed Wall --|tLes Paysagistes: expanding, producing, contested fields of landscape /|rEd Wall --|tDesigning momentums: site, practice, media as landscape /|rChristina Leigh Geros --|tOperational landscapes: hinterlands of the Capitalocene /|rNeil Brenner and Nikos Katsikis --|tTrash peaks: a terrarium of the anthropocene /|rRania Ghosn and El Hadi Jazairy --|tInwood's geofollies: and other witnesses of dissonance /|rTiago Torres-Campos --|tPelagic alphabet: islands as a model of the ocean /|rLuis Callejas and Charlotte Hansson --|tAdvanced landscapes: a structured pedagogy of process /|rEd Wall --|tMeal-deal ecologies: landscape thinking /|rHarry Bix --|tWorking place: constructing collage as critique /|rToya Peal --|tLandscape drift: something in the air tonight /|rNeil Spiller --|tTime portals, love machines, land oracles: hybrid geography and the situated digital /|rTim Waterman --|tLandscape city: infrastucture, natural systems and city-making /|rJames Corner --|tWhat is design now? Unmaking the landscape /|rKate Orff --|tFrom line to landscape: the Irish northwest border
region /|rGareth Doherty and Pol Fité Matamoros --|tAt a tangent: delineating a new ecological imaginary /|rMatthew Gandy --|tNation against nature: from the global border to the cross-border commons /|rTeddy Cruz and Fonna Forman -- |tNo design on stolen land: dismantling design's dehumanising White supremacy /|rPierre Bélanger --|tSt. Alfege: Hawksmoor speaking across time /|rNeil Spiller
"January/February 2020."
Includes bibliographical references
Keywords: Landscape architecture; Architecture, Modern -- 21st century; City planning